Ankle spanning external fixator with limited internal fixation for distal tibial extra-articular fractures - Goel, Siddharth; Elhence, Abhay (International Journal of Research in Medical Sciences, 2017)
Background: Fractures of the distal tibia are among the most difficult fractures to treat. The short distal segment presents difficulty in choosing the appropriate fixation method. The greatest challenge lies in the relatively tight soft tissue around the ankle. As a result, it has been a recent interest in treating these fractures with external fixation and limited internal fixation. The external stable fixation methods used are tubular or ring fixators, with or without immobilising the ankle. This minimally invasive nature of the surgery can avoid catastrophic wound complications like dehiscence, implant exposure and infection. Methods: 18 patients with extra-articular distal tibial fractures (AO Type 43A) were treated with the technique of ankle spanning external fixation. Lag screws or K-wires were supplemented for limited internal fixation when required. Fibula was stabilised in all cases. Intra- articular and Compound fractures were excluded. In addition to union at fracture site, ankle pain and motion was noted in each follow-up. Results: The mean follow-up was 25 months. Of the 18 patients included all but one fractures united with an average healing time of 16 to 18 weeks. Ankle pain and motion was graded according to Mazur modified by Teeny and Wiss clinical scoring system. 15 of them had excellent or good results, 2 had fair results. One patient had poor result. Five pin tract infections occurred. 17 patients had no evidence of osteoarthritis after completing follow up of at least 2 years. Conclusions: Distal tibial fractures are complex injuries, not only regarding the bony component, but also in terms of the management of the soft tissue problem. Ankle Spanning External Fixator with Limited Internal fixation is a relatively simple and cost-effective method for treating these fractures, achieving union and also maintaining ankle function.